Pengaruh Intensifikasi Kerja, Keseimbangan Kehidupan-Kerja, dan Fleksibilitas Kerja Terhadap Kepuasan Kerja Karyawan Milenial Perusahaan Startup Yang Berdomisili di RW 15 Kelurahan Rangkapan Jaya, Kecamatan Pancoran Mas, Kota Depok - Naura Indah Adiiba, (2022)
This quantitative study has the objective to determine the effect of work intensification, work-life balance, and work flexibility on job satisfaction of millennial start-up employees who are domiciled in RW 15, Rangapan Jaya Village, Kec. Pancoran Mas, Depok City. The population is employees of a startup company. The sample was obtained by 38 respondents, by applying the saturated sample method. Data analysis supported smartPLS 3.0 software using partial hypothesis testing (T-test) and simultaneous (F test). The results of the study are (1) there is a positive and significant effect of work intensification on employee job satisfaction, (2) there is a positive and significant effect of work-life balance on employee job satisfaction, (3) there is a positive and significant effect of work flexibility on employee job satisfaction, also (4) there is a significant effect of work intensification, work-life balance, and work flexibility on employee job satisfaction. Keywords : Work Intensification, Work-Life Balance, Work Flexibility, Job Satisfaction